Minimum traffic inter-BS SHO boundary selection algorithm for CDMA-based wireless networks - Abu-Amara, M. (2004)
An algorithm is presented to select an inter-base station soft handoff (inter-BS SHO) boundary for code division multiple access (CDMA)-based wireless networks. The selected inter-BS SHO boundary splits base transceiver systems (BTSs) equally over two BSs, and reduces the amount of links needed to support inter-BS SHO by minimizing the amount of traffic flow crossing the boundary. The algorithm has an O(n/sup 4/) running time, where n is the number of BTSs in the wireless network.